"Protenuria in SLE: Is it always lupus?". (April 2021) - Celia, Alessandra Ida; Priori, Roberta; Cerbelli, Bruna; Diomedi-Camassei, Francesca; Leuzzi, Vincenzo; Scrivo, Rossana; Alessandri, Cristiano; d'Amati, Giulia; Conti, Fabrizio
Proteinuria is one of the most typical manifestations of kidney involvement in Systemic Lupus Erythematosus (SLE). We report the case of a 23-year-old woman with a 6-year-long history of SLE presenting with proteinuria after a three-year remission on hydroxychloroquine. Kidney histological examination showed alterations inconsistent with lupus nephritis and suggestive of hydroxychloroquine toxicity or Fabry disease. The latter was confirmed by genetic assay.